(untitled) - Ohmae, Kenichi (New York, 1995)
Nations are becoming obsolete from an economic standpoint, declares Tokyo-based business consultant Ohmae (The Borderless World). He argues that the traditional nation-state, now beholden to domestic special interests, its government "an enemy of the public at large," has become an inefficient, even impossible, business unit in the new global economy. Instead of a world order based on discrete, independent nations, Ohmae envisions autonomous networks of what he calls "region states"?geographically linked economic zones that forge productive ties with the global marketplace by putting the right policies, information technology and infrastructure in place. Examples of emerging region states cited here are San Diego/Tijuana; Hong Kong and southern China; and northern Italy and the Rhine-Alps region of France. Although Ohmae overstates his case, his challenging primer gives managers, economists, politicians and policymakers new ways to think about global economic problems and opportunities.
Keywords: World politics,Democracy,National state,Quốc gia,Dân chủ,Chính trị thế giới; 1989-,1989-